Lotyniškojo šrifto įsigalėjimas lietuvių poligrafijoje - Užtupas, Vilius (Knygotyra, 1976)
At the very beginning of printing Johann Gutenberg and other printers of his time produced types closely imitating scripts written by goose-quill. The design of these script-types called the gothic type spread throughout Europe. The types of this design have been also used in printing the first Lithuanian books. But soon on the pages of printed books, particularly in their title-pages, there appeared types of a new design – the Latin (Roman) type, called also the Antiqua. In the Lithuanian books printed in Karaliaučius (Königsberg) and other East-Prussian printing shops the Antiqua-type is comparatively rare. The Gothic type is dominating here even until the second world-war. In the printing shops of Vilnius the Roman Antiqua has been gaining more and more ground and finally in the year 1767 had supplemented completely the Gothic type. This change has been strongly influenced by the bookprinting of some catholic neighbourcountries and among them in the first place – by the Polish press.